2019
DOI: 10.3390/nu11112733
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Iron Metabolism-Associated Dietary Pattern Predicts an Altered Body Composition and Metabolic Syndrome

Abstract: Diet plays an important role in the development of obesity and may contribute to dysregulated iron metabolism (DIM). A cross-sectional survey of 208 adults was conducted in Taipei Medical University Hospital (Taipei, Taiwan). A reduced-rank regression from 31 food groups was used for a dietary pattern analysis. DIM was defined as at least four of the following criteria: serum hepcidin (men >200 ng/mL and women >140 ng/mL), hyperferritinemia (serum ferritin of >300 ng/mL in men and >200 ng/mL in women), central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This pattern is associated with higher odds of T2DM and shares similar features with the RRR-derived DPs in the present analysis, being characterized by high consumption of starchy foods and low intake of fruits and vegetables [16]. The combination of condiments, margarine and higher glycemic index foods such potatoes may contribute to the observed associations with T2DM [42,43]. These foods characterize modernized diets, which are known to confer an unhealthy body composition and increased risk of T2DM [44].…”
Section: Dietary Patterns and Proxy Markers Of Nalfd And T2dmsupporting
confidence: 76%
“…This pattern is associated with higher odds of T2DM and shares similar features with the RRR-derived DPs in the present analysis, being characterized by high consumption of starchy foods and low intake of fruits and vegetables [16]. The combination of condiments, margarine and higher glycemic index foods such potatoes may contribute to the observed associations with T2DM [42,43]. These foods characterize modernized diets, which are known to confer an unhealthy body composition and increased risk of T2DM [44].…”
Section: Dietary Patterns and Proxy Markers Of Nalfd And T2dmsupporting
confidence: 76%
“…Recent studies have elucidated the relationship between fat distribution and iron status indicators [ 23 , 45 , 49 52 ]. Results of this study indicated a statistically significant increase (p < 0.05) in ferritin with an increase in android to gynoid fat ration for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, Cempaka et al showed a weak correlation between VS and ferritin. This association disappeared after adjusting for age, gender and BMI [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…No matter what similarities or differences are discovered, they may provide insight into components of diet that work toward better or worse health. In this endeavor, we reviewed data mining-related literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] pertaining to Taiwanese dietary patterns and multiple health or disease outcomes and also described the recent Taiwanese dietary content using data collected in the Nutrition and Health Survey in Taiwan from 2017 to 2020 in order to shed light on healthy eating patterns and options in Asians.…”
Section: Introductionmentioning
confidence: 99%